Influence of Y Substitutions on the Structural and Magnetic Properties of Mn-Zn Ferrites - Momin, AA; Munshi, Anis; Imran, TM; Hossain, Amir; Mimi, A; Gafur, MA; Hasan, HR; Hossain, AKM Akther (Jagannath University Journal of Science, 2024)
The ordinary solid-state reaction method has been used to produce polycrystalline Mn0.5Zn0.5Fe2–xYxO4. X-ray diffraction (XRD) and scanning electron microscopy (SEM) have been used to study the structural and surface morphology of the samples, respectively. The formation of cubic spinel crystal structure is observed in XRD patterns. The Nelson-Riley function is used to determine the lattice parameters. Vegard's rule is followed by the lattice parameter change with Y content in different Mn0.5Zn0.5Fe2–xYxO4. The x-ray density, and the bulk density both increase with Y content due to the higher atomic weight of Y compared to atomic weight of Fe, as well as porosity decreases. SEM micrographs demonstrate that the average grain size decreases with the increase of Y contents. When x = 0.05, the initial permeability shows maximum then starts to decrease for further increase of Y content. For the composition Mn0.5Zn0.5Fe1.95Y0.05O4, the relative quality factor (RQF) is found maximum (3477). With the increase of Y content, the peak value of the relative quality factor shifts to higher frequencies region which is the consequence of Snoek relation. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 53−63